Impaired antibody-mediated protection and defective IgA B cell memory in experimental infection of adults with respiratory syncytial virus - Habibi,MS; Jozwik,A; Makris,S; Dunning,J; Paras,A; DeVincenzo,JP; de,Haan CA; Wrammert,J; Openshaw,PJ; Chiu,C; The,MOSAIC Investigators (American Journal of Respiratory and Critical Care Medicine, 2015)
Rationale: Despite relative antigenic stability, respiratory syncytial virus (RSV) re-infects throughout life. After >40 years of research, no effective human vaccine exists and correlates of protection remain poorly defined. Most current vaccine candidates seek to induce high levels of RSV-specific serum neutralizing antibodies, which are associated with reduced RSV-related hospitalization rates in observational studies but may not actually prevent infection. Objectives: Characterize correlates of protection from infection and the generation of RSV-specific humoral memory to promote effective vaccine development. Methods: We inoculated 61 healthy adults with live RSV and studied protection from infection by serum and mucosal antibody. We analyzed RSV-specific peripheral blood plasmablast and memory B cell frequencies and antibody longevity. Measurements and Main Results: Despite moderately high levels of pre-existing serum antibody, 34 (56%) became infected, of whom 23 (68%) developed symptomatic colds. Prior RSV-specific nasal IgA correlated significantly more strongly with protection from PCR-confirmed infection than serum neutralizing antibody. Increases in virus-specific antibody titers were variable and transient in infected subjects, but correlated with plasmablasts that peaked around day 10. During convalescence, only IgG (and no IgA) RSV-specific memory B cells were detectable in peripheral blood. This contrasted with natural influenza infection, where virus-specific IgA memory B cells were readily recovered. Conclusions: This observed specific defect in IgA memory may partly explain RSV's ability to cause recurrent symptomatic infections. If so, vaccines able to induce durable RSV-specific IgA responses may be more protective than those generating systemic antibody alone.